2015
DOI: 10.1007/s10551-015-2612-6
|View full text |Cite
|
Sign up to set email alerts
|

Financial Disclosure and Customer Satisfaction: Do Companies Talking the Talk Actually Walk the Walk?

Abstract: Using the emerging technology of large-scale textual analysis, this study examines use of the term "customer satisfaction" and its variants in the principal annual financial reports issued by publicly-traded U.S. corporations and filed with the Securities and Exchange Commission as Form 10-K. We document the frequency of the term's occurrence in 10-Ks over the 1995 to 2013 period and differences in usage across industries. We then relate the term's usage in 10-Ks to subsequent scores from the American Customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…In fact, recent studies have identified narrative disclosure in 10‐K filings as a channel for managers to convey to market participants useful and important information about distinctive, yet latent, firm traits. For example, Balvers, Gaski and McDonald (2016) find that 10‐K filings feature important information that managers use to communicate the importance of customer satisfaction in their firms, whilst Li, Lundholm and Minnis (2013) find that they feature important information about the firm's competitive environment.…”
Section: Measures Construct Validity and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, recent studies have identified narrative disclosure in 10‐K filings as a channel for managers to convey to market participants useful and important information about distinctive, yet latent, firm traits. For example, Balvers, Gaski and McDonald (2016) find that 10‐K filings feature important information that managers use to communicate the importance of customer satisfaction in their firms, whilst Li, Lundholm and Minnis (2013) find that they feature important information about the firm's competitive environment.…”
Section: Measures Construct Validity and Hypothesesmentioning
confidence: 99%
“…Secondly, it enables the inspection of management's disclosure in the 10‐K filings, for which managers bear the fiduciary responsibility to communicate reliable and up‐to‐date firm‐specific information to shareholders. Thirdly, it is based on the bag‐of‐words method, which is simple and has been shown to be suitable for identifying latent firm traits from 10‐K filings (Audi, Loughran and McDonald, 2016; Balvers, Gaski and McDonald, 2016; Fiordelisi and Ricci, 2014; Li, Lundholm and Minnis, 2013; Loughran and McDonald, 2016; Merkley, 2013; Nguyen, Nguyen and Sila, 2019).…”
Section: Measures Construct Validity and Hypothesesmentioning
confidence: 99%
“…In the context of corporate culture, Audi et al (2016) “hypothesize that a more frequent count of 21 unique “trust” words, like trust , character , and virtue , in the MD&A [Management Discussion and Analysis] section of a firm’s 10-K indicates a corporate culture that involves greater trust”, especially if such firms also use audit and control-type words. Balvers et al (2016) document that “voluntary use by firms of monitoring and measurement of customer satisfaction is a credible signal that is associated with higher subsequent customer satisfaction”.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Si partimos de que la satisfacción del cliente es la principal norma para la teoría y la práctica del marketing y la gestión, es posible emplear series de tiempo que permitan dar seguimiento a los clientes, pues las empresas deben centrarse en su bienestar. Por lo tanto, es importante generar reportes de gestión (Balvers et al, 2015). En este sentido, debe buscarse la forma de tener indicativos que nos muestren si lo que se está haciendo en la empresa, en tanto a la satisfacción y lealtad del cliente, va bien o dónde va mal.…”
Section: La Importancia De La Satisfacción Del Clienteunclassified